Passagerer Herzschrittmacher - Graf, Matthias; Stiller, Patrick; Karch, Martin (DMW - Deutsche Medizinische Wochenschrift, 2018)
Symptomatic bradycardia is usually caused by abnormalities of atrioventricular conduction or sinus node dysfunction. Reversible and irreversible causes must be considered.Temporary pacemakers are used in the emergency treatment in case of severe bradyarrhythmia.They help to bridge the acute phase until spontaneous restoration of atrioventricular or sinus node function or –if spontaneous restoration fails- until a permanent pacemaker system was implanted.In the following article we discuss the commonly used temporary pacemaker systems. We demonstrate their use and correct programming by an illustrated step by step explanation. For troubleshooting a flow chart was added.
Keywords: Kardiologie; passagerer Herzschrittmacher; temporäre Schrittmacherstimulation